2015
DOI: 10.1016/j.ceb.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Desmin related disease: a matter of cell survival failure

Abstract: Maintenance of the highly organized striated muscle tissue requires a cell-wide dynamic network that through interactions with all vital cell structures, provides an effective mechanochemical integrator of morphology and function, absolutely necessary for intra- and intercellular coordination of all muscle functions. A good candidate for such a system is the desmin intermediate filament cytoskeletal network. Human desmin mutations and post-translational modifications cause disturbance of this network, thus lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
126
0
33

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(161 citation statements)
references
References 60 publications
(86 reference statements)
2
126
0
33
Order By: Relevance
“…We found abnormally high actin levels, suggesting a functional dependence among these three proteins in heart. Remarkably, Des −/− knockout and transgenic nebulette Q128R mice share atypical lysosomes, mitochondria, and intercalated disks (Bang and Chen, 2015; Capetanaki et al , 2015). To suggest that desmin–nebulette partnership may account for some of these defects in cardiomyocytes is tempting and requires further study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found abnormally high actin levels, suggesting a functional dependence among these three proteins in heart. Remarkably, Des −/− knockout and transgenic nebulette Q128R mice share atypical lysosomes, mitochondria, and intercalated disks (Bang and Chen, 2015; Capetanaki et al , 2015). To suggest that desmin–nebulette partnership may account for some of these defects in cardiomyocytes is tempting and requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…An anomaly of the desmin–nebulette interaction caused by a glutamic to aspartic acid mutation in desmin at position 245 underlies a human desminopathy (Vrabie et al , 2005; Strach et al , 2008; Conover et al , 2009). Desminopathies belong to a heterogeneous genetic disease entity, termed myofibrillar myopathies (MFMs), which are caused by at least 40 distinct desmin mutations and are characterized by the formation of desmin aggregates in striated muscle (van Spaendonck-Zwarts et al , 2011; Claeys and Fardeau, 2013; Clemen et al , 2013; Capetanaki et al , 2015). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The desmin scaffold is a primary target for cardiomyopathy and heart failure both in mice and humans (Goldfarb et al, 1998;Capetanaki et al, 2007Capetanaki et al, , 2015. Mice deficient for desmin develop both skeletal and myocardial defects that are strongly linked to impaired mitochondrial morphology and function (Milner et al, 1996(Milner et al, , 1999(Milner et al, , 2000Li et al, 1996;Papathanasiou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We showed that desmin, the muscle-specific IF protein, is a major target in TNFα-induced cardiomyopathy 21,22 . Specifically, desmin is cleaved by TNF-α-induced caspase-6, loses its proper ID localization and forms aggregates.…”
mentioning
confidence: 93%